ANALISIS MORFOFONEMIK CERITA PENDEK “PRODHUSER PETENG” KARYA OYOS DALAM MAJALAH PANJEBAR SEMANGAT NO.32 EDISI AGUSTUS 2021 - Aldo Diaz Febrianta; Mahendra Bimo Yudhanto (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
This study aims to reveal: (1) the morphophonemic process that occurs due to the morphological process in the short story Prodhuser Peteng by Oyos; (2) phonemes that undergo morphophonemic processes in the short story Prodhuser Peteng by Oyos. The type of research used in this study is qualitative descriptive research. The subject of this study is the short story Prodhuser Peteng by Oyos while the object of research used is the form of words that undergo morphophonemic processes. The main instrument in this study is the researcher himself who is supported by reference books as references. Data collection techniques use markup reading techniques and note-taking techniques. The data analysis technique in this study is a descriptive technique. The data presentation technique used in this study is an informal method. The results of this study indicate, (1) the morphophonemic process that occurs due to the morphological process is divided into three, namely the addition of phonemes, changes in phonemes, and removal of phonemes; (2) phonemes that undergo morphophonemic processes include the phonemes /a/, /b/, /c/, /d/, /dh/, /e/, /g/, /j/, /k/, /l/, /o/, /p/, /r/, /s/, /t/, /u/ and /w/.